Analytical quality by design in the development of a cyclodextrin‐modified capillary electrophoresis method for the assay of metformin and its related substances. Issue 17 (14th July 2014) - Orlandini, Serena; Pasquini, Benedetta; Gotti, Roberto; Giuffrida, Alessandro; Paternostro, Ferdinando; Furlanetto, Sandra
<x xml:space="preserve">Abstract</x> Quality by Design (QbD) is a new paradigm of quality to be applied to pharmaceutical products and processes, recently encouraged by International Conference on Harmonisation guidelines. In this paper QbD approach was applied to the development of a CE method for the simultaneous assay of metformin hydrochloride (MET) and its main impurities. QbD strategy was focused on electrophoretic process understanding, and the analytical method was thoroughly evaluated by applying risk assessment and chemometric tools. Method scouting allowed CD‐CZE based on the addition of carboxymethyl‐β‐CD to Britton‐Robinson acidic buffer to be chosen as operative mode. Seven critical process parameters (CPPs) were selected, related to capillary, injection, BGE and instrumental settings. The effect of the different levels of the CPPs on critical quality attributes (CQAs), e.g. critical resolution values and analysis time, was evaluated in a screening study. Response surface methodology led to draw contour plots and sweet spot plots. The definition of design space was accomplished by applying Monte‐Carlo simulations, thus identifying by risk of failure maps a multivariate zone where the CQAs fulfilled the requirements with a selected probability. Finally, a control strategy was designed and the method was applied to a real sample of MET tablets.